Development of Qr-Code Media-Based Modules in Constructing Learning to Increase Learning Motivation - Kandiri, Kandiri; Nurwahidin, Muhammad; Aransyah, Ade; Purmadi, Ary (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
Education plays an important role in preparing the younger generation to face the challenges of the 21st century. One innovation in education is the development of QR-Code media-based modules to increase student learning motivation. QR-Code technology allows teachers to present learning materials in an interactive and interesting way, thus increasing student involvement in the learning process. In addition, QR-Code-based modules also allow easy and practical access for students in learning materials inside and outside the classroom. By utilizing this digital technology, teachers can provide a more engaging and effective learning experience for students, thus supporting the development of 21st century skills required in an ever-evolving world. Therefore, it is important for educators to continue to develop and utilize technology in providing innovative and relevant learning resources for learners.